Goalkeeper's eggbeater kick in waterpolo: Kinematics, dynamics and muscular coordination - Klauck, J.; Daniel, K.; Bayat, M. (Biomechanics and Medicine in Swimming X, 2006)
By using a Doppler-Ultrasound-Velocimeter System yielding the vertical speed of a goalkeeper's head during different actions in waterpolo the kinetics of the total body could be determined approximately. Synchronous measurements of the electrical activity of Mmi. glutaeus maximus, vastus medialis and adductor longus were taken to study the muscular coordination during the execution of the eggbeater kick. This leg kick could produce climbing heights up to 0,7 m; the vertical speed varying from +/- 0,8 m/s to 2 m/s. The muscle activation pattern showed a clearly defined order of appearance in time, announcing a high potential of muscular fatigue.